فقه اللغة العربية من خلال كتاب عن اللسان وفي البيان للدكتور - مختار نويوات- وصف ونقد - لينا بن سلطان (My University, 2026)
Abstract This study addresses the subject of Arabic philology and its contemporary issues through a descriptive and critical reading of the book "On Tongue and Eloquence" (An al-Lisan wa fi al-Bayan) by Dr. Mokhtar Nouiouat. The research is divided into two chapters. The first chapter is dedicated to the theoretical framework, clarifying the concept of philology among ancient and modern scholars, and its relationship with linguistics, while explaining its phonetic, morphological, syntactic, and semantic levels. The second chapter adopts an applied and critical approach, tracking the book's eleven articles. Through these articles, vital issues are discussed, such as the translation crisis, methods of language acquisition away from grammatical complexities, and the evolution of the Arabic language. Additionally, it critiques lexical gaps, the risk of cultural isolation, and analyzes the author's stylistic approach in his essays. The study concludes with a final section summarizing the most prominent results and recommendations reached -------------------------- ملخص تناولت هذه الدراسة موضوع فقه اللغة العربية وقضاياه المعاصرة من خلال قراءة وصفية، نقدية لكتاب "عن اللسان وفي البيان" للدكتور مختار نويوات. وقد قسّمتُ البحث إلى فصلين؛ خصصتُ الفصل الأول للجانب النظري، حيث وضَّحتُ فيه مفهوم فقه اللغة عند القدامى والمحدثين، وعلاقته باللسانيات، مع شرح مستوياته الصوتية والصرفية والنحوية والدلالية. أمَّا الفصل الثاني فكان تطبيقياً ونقدياً، تتبعتُ فيه المقالات الإحدى عشرة للكتاب، وناقشتُ من خلالها قضايا حيوية مثل أزمة الترجمة، وطرق اكتساب اللغة بعيداً عن تعقيد النحو، وتطور العربية، بالإضافة إلى نقد الثغرات المعجمية وخطر العزلة الثقافية، وصولاً إلى تحليل أسلوب الكاتب في مقالاته، لتنتهي الدراسة بخاتمة تلخص أبرز النتائج والتوصيات التي توصلتُ إليها. ------------------------- Résumé « Cette étude a abordé le thème de la philologie arabe et de ses enjeux contemporains à travers une lecture descriptive et critique du livre « De la langue et de l'éloquence » (An-Lissan wa fi Al-Bayan) du Dr Mokhtar Nouiouat. J'ai divisé cette recherche en deux chapitres : le premier a été consacré au volet théorique, dans lequel j'ai clarifié le concept de philologie chez les anciens et les modernes, ainsi que sa relation avec la linguistique, tout en explicitant ses niveaux phonétique, morphologique et syntaxique. Quant au second chapitre, pratique et critique, j'y ai suivi les onze articles du livre, à travers lesquels j'ai traité de questions vitales telles que la crise de la traduction, les méthodes d'apprentissage de la langue loin de la complexité de la grammaire, et l'évolution de la langue arabe, en plus de la critique des lacunes lexicales et du risque d'isolement culturel, pour arriver enfin à l'analyse du style de l'auteur dans ses articles. L'étude se conclut par une synthèse reprenant les principaux résultats et recommandations auxquels je suis parvenu(e). »
Keywords: • Arabic Philology; Linguistics; Mokhtar Nouiouat; Language Acquisition; Literary Criticism; فقه اللغة العربية، اللسانيات، مختار نويوات، اكتساب اللغة، النقد الأدبي.; • Philologie Arabe; Linguistique; Acquisition du langage; Critique littéraire